Fatigue crack initiation and propagation in lotus-type porous material (Fracture and Structural Integrity, 2015)
The investigation of fatigue strength of lotus-type structure with nodular cast iron as a base material using computational model is analysed in present study. The irregular pores distribution in transversal and longitudinal direction, regarding the external loading, is considered in the computational models. The complete fatigue process of analyzed porous structure is then divided into the crack initiation (Ni) and crack propagation (Np) period where the total fatigue life (N) is defined as: N = Ni + Np. The crack initiation period is determined using strain life approach where elastic-plastic numerical analysis is performed to obtain the total strain amplitude in the critical stress fields around the pores. The simplified universal slope method is then used to determine the number of stress cycles, Ni, required for formation of initial cracks. The number of stress cycles, Np, required for crack propagation from initial to the critical crack length is also numerically determined using finite element (FE) models, in the frame of Abaqus computation FEM code. The maximum tensile stress (MTS) criterion is considered when analyzing the crack path inside the porous structure. The performed computational analyses show that stress concentrations around individual pores are higher when external loading is acting in transversal direction in respect to the pore distribution. Therefore, further computational analyses regarding crack initiation and crack propagation period have been done only for pores distribution in transversal direction.
Keywords: Lotus-type porous structures; Fatigue crack initiation; Fatigue crack propagation; Numerical analysis